24 crossing limit cycles in only one nest for piecewise cubic systems. (May 2020) - Gouveia, Luiz F.S.; Torregrosa, Joan
Abstract: In this work, we are interested in crossing limit cycles surrounding only one equilibrium point or a sliding segment. The studied systems are piecewise cubic polynomial defined in two zones separated by a straight line. In this class, we get at least 24 crossing limit cycles, all of them in only one nest, bifurcating from a cubic polynomial center. The computations use a parallelization algorithm.